Application of a Learning Model Based on Scientific Literacy to Improve Reasoning Ability Students' Critical Thinking - Siagian, Gunaria; Gunawan , Revi Gina; Festiyed; Asrizal; Skunda; Desnita (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
The purpose of this study was to apply a scientific literacy-based learning model to improve students' critical thinking reasoning abilities in class X SMA Negeri 3 Pematangsiantar. The method used in this study is a Quasi Experimental Design quantitative research method. The results of the study show that the application of scientific literacy-based learning models can improve students' critical thinking reasoning abilities. The hypothesis in this study is that there is an increase in students' critical thinking reasoning abilities in class X SMA Negeri 3 Pematangsiantar. Based on the results of calculations using the t test, it can be concluded that the hypothesis is accepted, namely t_count of 6.217 greater than ttable of 2.002. The results of this study are expected to be useful for related parties such as teachers and further researchers.